Adolescent gynaecology - Michala, L.; Creighton, S.M. (Obstetrics, Gynaecology and Reproductive Medicine, 2008)
Adolescent gynaecology is increasingly recognized as an area in which specific knowledge and expertise is required to ensure the best outcome. Gynaecological problems in adolescents are common and, although serious disease is rare, distress and discomfort can be significant. Adolescent girls are under great pressure, particularly in terms of examination performance, and problems such as menstrual dysfunction can be particularly difficult to manage. Careful and sympathetic assessment is crucial, and simple treatment remedies may be sufficient. Complex and rare medical conditions can also occur and must not be missed. Some congenital disorders present for the first time in adolescence. Early detection and appropriate treatment ensures the best possible outcome in terms of sexual function and potential fertility. © 2008 Elsevier Ltd. All rights reserved.
Keywords: Adolescent gynaecology; Menstrual dysfunction; Polycystic ovary syndrome; Rokitansky syndrome; Turner syndrome